The impact of Economic, Social, and Good Corporate Governance (ESG) on Growth Opportunities (GO) in ESG companies listed on the Indonesia Stock Exchange: english - Rachmad, Jenneta Virenna; Sung Suk, Kim (Enrichment : Journal of Management, 2023)
The impact of Economic, Social, and Governance (ESG) practices on companies listed on the Indonesia Stock Exchange. ESG influences strategic execution and long-term value creation. Growing societal awareness urges businesses to prioritize not only profits but also social and environmental implications. Government mandates, notably Indonesia's Financial Services Authority (OJK), stress ESG disclosure's importance. The research delves into the intricate relationship between ESG and Growth Opportunities (GO), emphasizing alignment with good governance standards, positive effects on reputation, and GO as a metric for future returns. This study underscores stakeholder engagement, community legitimacy through ESG disclosure, and the interplay between ESG and GO in sustainable value creation for investors, policymakers, and businesses amid Indonesian market challenges.